Characteristics of physical loads endured by military officers of mechanized troops during field maneuvres - I.L. Shlyamar; A.I. Yaworsky; S.V. Romanchuk; A.P. Petruk; V.V. Dzyama; I.V. Romaniv; A.S. Vorontsov (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: observation over influence of physical loads on military officers in process of acquiring and mastering of military applied skills during field maneuvers. Material: in experiment 120 military officers of 20-25 years old age with equal physical fitness participated. Results: it was determined that in period of field maneuvers the greatest load was endured by military officers in attack exercises and on the march. The least physical loads were in period of organization and fulfillment of combat shooting. It was also established that main part of motor actions was fulfilled in aerobic mode. Military officers' functioning in field maneuvers was accompanied by heart beats rate of 120-150 b.p.m. and 60-90 b.p.m. during long time. Conclusions: We offered to practice physical training of mechanized units' military officers in modes, close to field ones.